We can find the distance between two points using the distance formula:
[tex]\sqrt{(x.2 - x.1)^{2} + (y.2 - y.1)^{2}}[/tex]
√(-1 - 6)^2 + (14 - 16)^2
√53 = 7.3
Answer:
√53 units.
Step-by-step explanation:
By the distance formula,
The distance between the points [tex]A(x_1, y_1)[/tex] and [tex]B(x_2, y_2)[/tex] is,
[tex]AB=\sqrt{(x_2-x_1)^2+(y_2-y_1)^2}[/tex]
Thus, the distance between the points M(6,16) and Z(-1,14),
[tex]MZ=\sqrt{(-1-6)^2+(14-16)^2}[/tex]
[tex]=\sqrt{(-7)^2+(-2)^2}[/tex]
[tex]=\sqrt{49+4}[/tex]
[tex]=\sqrt{53}\text{ units}[/tex]